Case report of endoscopic treatment of sigmoid gallstone ileus - I Molnar; T Shynkaryk; E Prykhodko; V Perepadya (Perioperative Medicine)
Gallstone disease affects more than 6 % of the global population. Initially, it often presents asymptomatically, but the risk of complications increases over time. One rare complication of gallstone disease is intestinal obstruction caused by the blockage of the intestinal lumen, also referred to in foreign literature as “gallstone ileus”. According to international sources on Pubmed, Google Scholar, and Web Of Science, the frequency of “gallstone ileus” is 0.5 % of all gastrointestinal complications. We present a clinical case of a patient with clinical and diagnostic evidence of intestinal obstruction. Patient V., aged 86, was diagnosed with CT signs of a sigmoid neoplasm and a polyp in the cecum, along with intestinal obstruction during an outpatient examination. The patient was referred for intraintestinal stenting. During an attempt to perform a video colonoscopy, multiple diverticula with signs of diverticulitis and narrowing of the lumen of the sigmoid colon were observed in the distal parts of the sigmoid colon. A black foreign body (stone) was found in the area of narrowing. After displacing the stone, a flow of liquid stool was obtained, and 2.5 liters of liquid stool were aspirated. The foreign body was captured using a 4.5 cm Retrieval Net and, with difficulty, removed in the area of narrowing. Following this, a control video colonoscopy showed that the patency of the sigmoid colon was restored.